If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(3x + 6) = 21x + -10 Reorder the terms: 7(6 + 3x) = 21x + -10 (6 * 7 + 3x * 7) = 21x + -10 (42 + 21x) = 21x + -10 Reorder the terms: 42 + 21x = -10 + 21x Add '-21x' to each side of the equation. 42 + 21x + -21x = -10 + 21x + -21x Combine like terms: 21x + -21x = 0 42 + 0 = -10 + 21x + -21x 42 = -10 + 21x + -21x Combine like terms: 21x + -21x = 0 42 = -10 + 0 42 = -10 Solving 42 = -10 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| (p+7)(-2)= | | -33=5(v-3)-2v | | x=-1/2*4 | | 8.99(x)=1050+335 | | -(3r-2)=-4-4r | | -5y+8=10+y | | x+3-3(5x+15)=5 | | -4+3x=-6+10x | | 12x^2y^4-3x^5+9x^3y^2=0 | | 6x+234= | | -x+33=2x+15 | | a=(3x^2y^3)(5xy^2) | | -3(1-2x)=47-x | | Solve-3(2x-9)=-3 | | 4x+6y=-132 | | 3-2x=5(3+x) | | 6+2x=2x+6 | | 9n-7=4n+8 | | 10x-50+50=-15+50 | | 23-4x=7-8x | | 12x=18-2x | | -x+1=2x+13 | | -3x-25+15x=8+15 | | -10(v+3)=-25 | | 3(r+4)-6r=-9(-3) | | -2x^2m^2(m^2-4m)= | | x+102=4x | | -7+n=3n+1 | | 75h+10= | | 15+1.50x=45 | | 14=n+8+5n | | 10x-50=-15 |